A numerical study of cavitation and bubble dynamics in liquid CO2 near the critical point. (November 2016) - Pham, H.S.; Alpy, N.; Mensah, S.; Tothill, M.; Ferrasse, J.H.; Boutin, O.; Quenaut, J.; Rodriguez, G.; Saez, M.
Highlights: Thermal effects mechanism is found to strongly impede the bubble dynamics. A model for the bubble collapse in liquid CO2 is proposed and benchmarked. Slow bubble contraction with no noticeable pressure rise is predicted. Heat flux in the vapor region is highlighted to alter the rate of phase change. Results are seen to be in line with the observation in a previous experiment. Abstract: This study aims to provide insights into the cavitation and bubble dynamics in liquid CO2 near the critical point. It is inspired by a previous work that reports the absence of dysfunctional behavior during the operation of a test compressor in the two-phase region of CO2 . First, several characteristic parameters in the literature have suggested that thermal effects have significant impact on the dynamics of a CO2 bubble. These effects lead to the change of vapor pressure inside the bubble, impeding the motion of the bubble interface. As a consequence, the CO2 bubble collapse should feature a slow contraction of the bubble interface and the absence of noticeable pressure rise. In addition, a dynamic model has been proposed to quantitatively study the bubble collapse in liquid CO2 near the critical point. Simulation results have confirmed the qualitative prediction given by characteristic parameters. They have also revealed that the thermal layer inside the bubble has an important contribution to the bubble dynamics, in addition to the one outside the bubble, by altering the rate of phase change at the interface. These predicted results appear to be in line with the aforementioned experimental observations.